Non-invasive assessment of functional strain lines in the real human left ventricle via speckle tracking echocardiography. Issue 3 (5th February 2015) - Evangelista, A.; Gabriele, S.; Nardinocchi, P.; Piras, P.; Puddu, P.E.; Teresi, L.; Torromeo, C.; Varano, V.
Abstract A mechanics-based analysis of data from three-dimensional speckle tracking echocardiography is proposed, aimed at investigating deformations in myocardium and at assessing shape and function of distinct strain lines corresponding to the principal strain lines of the cardiac tissue. The analysis is based on the application of a protocol of measurement of the endocardial and epicardial principal strain lines, which was already tested on simulated left ventricles. In contrast with similar studies, it is established that endocardial principal strain lines cannot be identified with any structural fibers, not even along the systolic phase and is suggested that it is due to the capacity of the endocardial surface to contrast the dilation of the left ventricle.